Challenges Faced In Teaching English To Young Learners: A Case Study of Gresik Islamic School - Nurseha, Ivan (JEET, Journal of English Education and Technology, 2023)
Teaching English to students who lack prior knowledge, have a different first language, and possess diverse cultural backgrounds presents a significant challenge. This study employed a case study design to explore the perspectives of teachers regarding the instruction of English to young learners attending an Islamic school in Gresik, Indonesia. The study involved six English teachers from the selected school as participants. A qualitative methodology was utilized, and data were collected through interviews. The findings indicate that the teachers who participated in the study faced various challenges during their teaching, including (1) limited prior knowledge of English, (2) lack of motivation, (3) negative attitudes towards the English language, (4) time constraints for English study, (5) inadequate teaching and learning resources, (6) disorderly classroom environments, and (7) speaking anxiety. With assistance from others, the creativity of teachers, and collaborations with their peers, the teaching and learning process can be facilitated under certain conditions.